What is the relationship between microorganisms in the human body and upper tract urothelial carcinoma? - Pei, Xin; Yu, Minghui; Wang, Yijia; Zong, Shi; Qi, Fei; Wang, Kaichen (Frontiers in Immunology, 2025)
Upper Tract Urothelial Carcinoma (UTUC) is a highly malignant tumor originating from the epithelium of the upper urinary tract with diverse pathogenesis, but currently available diagnostic and therapeutic strategies have some limitations. In recent years, human microbiome-related studies have provided new ideas for the exploration of the pathogenesis and treatment of UTUC. In this paper, we review the research progress of human microbiome related to UTUC. Focusing on the urinary microbiome, the role of the microbiome in the pathogenesis of UTUC is investigated through the mechanisms of chronic inflammation, genotoxic damage, immune microenvironmental imbalance and metabolic reprogramming. The pyelo-ureteric microbiome of healthy populations is dominated by commensal bacteria such as Lactobacillus and Streptococcus, whereas pathogenic bacteria such as Escherichia coli (E. coli) and Enterococcus faecalis are significantly enriched in patients with UTUC, which results in the development of DNA damage, inflammatory response and immunosuppression. In addition, microbiome metabolites (e.g., short-chain fatty acids, tryptophan derivatives) can influence tumor progression by modulating immune checkpoints (e.g., PD-1/PD-L1, B7-H4) and metabolic pathways (e.g., Warburg effect). In diagnostic and therapeutic applications, urinary microbial markers (e.g., E. coli-specific gene clusters) can be combined with circulating tumor DNA (ctDNA) assays to improve diagnostic sensitivity and specificity, and indices of intestinal flora diversity (e.g., Simpson’s index) are significantly correlated with the response rate to chemotherapy and prognostic course. In the future, we need to overcome the challenges of difficult sample acquisition, unknown causal mechanisms, and etiologic heterogeneity interference, and promote multi-omics joint modeling as well as cross-ethnicity and geographic research, and bidirectional regulation mechanisms of the gut-kidney axis in order to develop more accurate UTUC diagnosis and treatment strategies.